Correlation Analysis of Anxiety and Mathematical Self-Efficacy on Problem Solving Ability Class XI IPA SMAN 2 Rumbiojaya - Wina Jamalia; Adityawarman Hidayat; Kasman Ediputra (Universitas Muhammadiyah Enrekang, 2023)
Solving math problems is important in learning mathematics. In fact, there are still many students who do not like mathematics. This is due, among other things, to the difficulty of understanding mathematics. These difficulties have an impact on student learning outcomes. Student learning outcomes can be optimal if students believe in their abilities. Confidence that students lack can cause anxiety. Anxiety is considered as one of the inhibiting factors in solving math problems. This is what prompted the researcher to conduct a study entitled